Oral Astragalus Root Supplementation for Mild to Moderate Chronic Kidney Disease: A Self-Controlled Case-Series - Yoshino, Tetsuhiro; Horiba, Yuko; Mimura, Masaru; Watanabe, Kenji (Frontiers in Pharmacology, 2022)
In this self-controlled case series, we aimed to investigate the variation in estimated glomerular filtration rate (eGFR) after taking astragalus-containing preparations in patients with mild to moderate chronic kidney disease (CKD) by retrospectively reviewing their charts in our clinic. We set the inclusion criteria as first-visit patients aged 20 years or older presenting to our clinic between October 1, 2014, and June 31, 2019, and who were prescribed astragalus-containing herbal preparations for any reason. We calculated the mean eGFR from the readings taken six months before (pre) and after (post) the intake of astragalus-containing preparations for each participant. Among the 37 patients included in our final analysis, we found a statistically significant improvement in the eGFR after prescribing astragalus-containing preparations (pre, 66 ± 12 mL/min/1.73 m2 vs. post, 70 ± 14 mL/min/1.73 m2; p<0.001 by paired t-test). Our results were consistent regardless of age, sex, CKD stage of the participants (G2 or G3), daily dosage of astragalus root, or duration of astragalus-containing preparations. No severe adverse reactions were recorded in the charts of the study participants. Our results suggest that there is eGFR improvement after taking astragalus-containing preparations in mild to moderate CKD cases as reported previously. The findings should be considered with caution due to major limitations such as small sample size without optimum control, short follow-up period, and incomplete data. Further adequately powered and designed studies are needed to confirm the efficacy and safety of the long-term use of astragalus root in patients with mild to moderate CKD.